Pengamanan Data Menggunakan Kriptografi EC Signcryption dan Steganografi Least Significant Bit (LSB) - Triasanti, Dini (Jurnal Ilmiah Teknologi dan Rekayasa, 2014)
The study aims at developing multiple security system of data namely data signcryption (signature-encryption). The concealment of the encryptioned data in text, or image, or audio, or video. In the study, the cryptograph method used is Elliptic Curve Signcryption, while steganograph used is modificated LSB (Least Significant Bit) method. The system is succeed to be developed using Java program, embedding and retrieving operation can be done fast, it is not significantly depended on the change of stego file. From the side of HVS, HAS, and the combination, there is no change of picture and audio quality in stego file, compress fiture, encryption and signature (signcrypt), as well as the steganograph can provide multi-protection of data.Keywords: Cryptograph, Steganograph, Elliptic Curve Signcryption, Least Significant Bit, Java.